Odpowiedź :
y=[x+1]²-4 y=-x-3 x²+2x+1-4=-x-3 x²+2x+1-4+x+3=0 x²+3x=0 Δ=b²-4ac=9-12=-3 Δ<0 →układ równań nie ma rozwiązania pozdrawiam
y=(x+1)²-4
y=-x-3
y=x²+2*x*1+1²-4
x=-3-y
y=(-3-y)²+2*(-3-y)-3
x=-3-y
y=-3²-2*(-3)*y*y²-6-2y-3
x=-3-y
y=9+6y*y²-6-2y-3
x=-3-y
y=4y*y²
x=-3-y
y nie może równać się 4y*y², układ równań sprzeczny.
y=-x-3
y=x²+2*x*1+1²-4
x=-3-y
y=(-3-y)²+2*(-3-y)-3
x=-3-y
y=-3²-2*(-3)*y*y²-6-2y-3
x=-3-y
y=9+6y*y²-6-2y-3
x=-3-y
y=4y*y²
x=-3-y
y nie może równać się 4y*y², układ równań sprzeczny.
y=(x+1)²-4
y=-x-3
y=x²+2x+1-4
y=-x-3
y=x²+2x+1-4
x=-3-y
y=(-3-y)²+2(-3-y)+1-4
x=-3-y
y=9-6y+y²-6-2y+1-4
x=-3-y
y+6y-y²+2y=-4+1-6+9
x=-3-y
9y-y²=0
x=-3-y
y=0
x=-3-0
y=0
x=-3
y=-x-3
y=x²+2x+1-4
y=-x-3
y=x²+2x+1-4
x=-3-y
y=(-3-y)²+2(-3-y)+1-4
x=-3-y
y=9-6y+y²-6-2y+1-4
x=-3-y
y+6y-y²+2y=-4+1-6+9
x=-3-y
9y-y²=0
x=-3-y
y=0
x=-3-0
y=0
x=-3